Beyond 'invisibility': queer intelligibility and symbolic annihilation in healthcare. Issue 1 (2nd January 2018) - Müller, Alex
Abstract: Sexual minority health is increasingly receiving attention by health sciences education and healthcare, with the core argument being that health can be improved by challenging sexual minority invisibility. Invisibility as a concept, however, does not allow for a deeper theoretical engagement with the reasons and consequences of the lack of representation of queerness in healthcare. Drawing on empirical research with queer healthcare users in South Africa, I argue that 'invisibility' actually encompasses two distinct, though related, concepts: queer symbolic annihilation as the reason for the exclusion of queer identities in health professions education and, by consequence, in healthcare; and queer (un)intelligibility as the consequence of this systemic erasure. By simply attributing discriminatory healthcare experiences of queer people to 'invisibility' we are missing opportunities to address underlying issues of queer symbolic annihilation and unintelligibility.